Peran Sintaksis dalam Pembentukan Kalimat Efektif pada Surat Lamaran Pekerjaan Bahasa Indonesia - Jelice Twista Sijabat; Novisya Nayla; Fitria Wulandari; Maikel Brekana Ginting; Sari Handayani Berutu; Anggia Puteri; Frinawaty Lestarina Barus (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Writing an effective job application letter requires a deep understanding of the syntactic structure of the Indonesian language. This article aims to examine the role of syntax in forming effective sentences in job application letters. The research was conducted through a literature review method with a qualitative descriptive approach. Data sources were obtained from various journals, articles, and relevant books on syntax, effective sentences, and the structure of application letters. The results of the study indicate that syntactic elements such as subjects, predicates, objects, complements, and adverbs play a central role in forming communicative, logical, and professional sentences. Common errors such as inappropriate sentence structure, incorrect use of conjunctions, non-standard diction, and ambiguity and inaccuracy of punctuation interfere with the effectiveness of communication in application letters. Therefore, the application of correct syntactic rules not only improves linguistic quality but also strengthens the professional image of applicants.